How Does Privatization Work? : Ownership Concentration and Enterprise Performance in Ukraine - Pivovarsky, Alexander (IMF Working Papers; Working Paper ;, 2001)
This paper investigates the relationship between ownership concentration and enterprise performance in Ukraine. Using data on 376 medium and large enterprises, it finds that ownership concentration is positively associated with enterprise performance in Ukraine. The paper also finds that concentration of ownership by foreign companies and banks is associated with better performance than ownership concentrated by the domestic owners. Ownership by Ukrainian investment funds and holding companies does not have a positive effect on performance. In contrast to predictions by many observers of early transition, privatization methods had a lasting effect on ownership structure in Ukraine.